1977
DOI: 10.1080/0002889778507925
|View full text |Cite
|
Sign up to set email alerts
|

Time as a factor in atmospheric sampling

Abstract: Differences in results of simultaneous air monitoring of ozone with three different methods in the field are described. The argument is advanced that the differences are due largely to sampling turbulent atmospheres with instruments utilizing different sampling intervals and time constants. It is concluded that when sampling natural turbulent atmospheres, a stable mean value can only be achieved through integrated sampling periods of greater than ten minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A statistical evaluation of a total ozone sampling network has been reported by Moxim (336). In two separate papers Sevirs and co-workers have concluded that in sampling turbulent atmospheres for ozone, sampling periods of 10 min or greater are required to produce representative data (422,423).…”
Section: Atmospherementioning
confidence: 99%
“…A statistical evaluation of a total ozone sampling network has been reported by Moxim (336). In two separate papers Sevirs and co-workers have concluded that in sampling turbulent atmospheres for ozone, sampling periods of 10 min or greater are required to produce representative data (422,423).…”
Section: Atmospherementioning
confidence: 99%
“…Indeed, substantial deviations between the results of instrumental electrochemical oxidant analyzers and measurements based upon other instrumental techniques have been demonstrated, 8991 although these may be due in part to differences in instrumental response times. 91 In view of the problems with the KI method, it is not surprising that the report by Negerbradt et al 92 that the chemiluminescent ozone-ethene reaction could be used for continuous monitoring of atmospheric ozone was followed rapidly by commercial production of analyzers based upon this measurement principle. Ambient air and ethene from a cylinder enter a reaction vessel at atmospheric pressure through concentric tubes facing a photomultiplier tube.…”
Section: Ozonementioning
confidence: 98%
“…In contrast, the absorption of ozone in neutral buffered 1% potassium iodide yielded 15-30% more iodine than that found by the BKI method or predicated by the stoichiometric equation: O 3 + 2I~ + 2H+ = I 2 + H 2 O + O 2 . Three different methods for measuring the ozone content of the atmosphere are employed simultaneously by Severs, et al 219 in order to study different sampling periods as a factor in the results. The continuous methods under test were photometric UV absorption, gas-phase (ethylene) chemiluminescence, and the neutral buffered potassium iodide method.…”
Section: Ozone (Oxidants)mentioning
confidence: 99%